Transcreation as a Way to Promote Employability in Translation Training: Adding Value to Translation Training - Morón Martín, Marián (HERMES - Journal of Language and Communication in Business, 2020)
An overview of the current professional translation industry shows that translation, in general, seems to be accommodating changes in the labor market and in society with relative ease. However, the scope, limits and boundaries of translation are a matter of academic and professional concern (Mayoral 2001; Tymoczko 2005/2007; Koskinen/Dam 2016; Dam et al. 2018), with some viewing the identity of translation somehow jeopardized by the great variety of professional translation-related services and practices encountered within the field (Gambier 2016; Koskinen/Dam 2016; Dam et al. 2018). It is true that services now associated with translation, such as technical communication (Risku 2004), transcreation, postediting or multilingual copyrighting (Mangell et al. 2019) are closely interrelated, sometimes even being identified as translation per se (Gambier 2016; Dam et al. 2018), despite the fact that no linguistic transfer even occurs. This paper will address the experience of trainee participants in a transcreation project developed at the University Pablo de Olavide in Seville (Spain). The project was an attempt to introduce transcreation, defined by the LSP industry as a service of added value, and initiate students in inventiveness and creative translation, while creatively enhancing translation graduates’ employability (Rojo/Meseguer 2018: 79). Despite the assumed role of universities as providers of employability skills, this initiative also aims to add value to translator training, adopting an open, creative and boundaryless approach when dealing with employability issues in translators’ training (Calvo 2010; Morón 2010; Kuznik 2016; Calvo 2018). The boundaries within and around the translation profession (Koskinen/Dam 2016) are tackled, through students completing simulated professional practice and self-reflection (Kiraly 2013/2016; Leggot/Stapleford 2004a/b). A qualitative and analytical approach will be adopted, presenting the final assessment results from trainee participants during Stage 1 of project implementation, as well as real testimonies of graduates and professionals reflecting on the impact the initiative has on trainees’ employability.